2014
DOI: 10.1088/1367-2630/16/4/043031
|View full text |Cite
|
Sign up to set email alerts
|

The role of space charge in spin-resolved photoemission experiments

Abstract: Spin-resolved photoemission is one of the most direct ways of measuring the magnetization of a ferromagnet. If all valence band electrons contribute, the measured average spin polarization is proportional to the magnetization. This is even the case if electronic excitations are present, and thus is of particular interest for studying the response of the magnetization to a pump laser pulse. Here, we demonstrate the feasibility of ultrafast spin-resolved photoemission using free electron laser (FEL) radiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…For normalization, the sample's magnetic orientation is reversed between bursts by magnetic field pulses. The 3000 X-ray pulses in one second may excite just a few electrons per pulse in order to avoid the influence of space charge in the electron analyzer optics [88]. The transmission of the electron analyzer was increased by a high pass energy of 100 eV and a larger entrance slit thus measuring an energy band of 5 eV.…”
Section: Ultrafast Spin Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…For normalization, the sample's magnetic orientation is reversed between bursts by magnetic field pulses. The 3000 X-ray pulses in one second may excite just a few electrons per pulse in order to avoid the influence of space charge in the electron analyzer optics [88]. The transmission of the electron analyzer was increased by a high pass energy of 100 eV and a larger entrance slit thus measuring an energy band of 5 eV.…”
Section: Ultrafast Spin Processesmentioning
confidence: 99%
“…Despite the poor statistics, this pilot study demonstrated that multi-hit spin analysis is possible in principle. However, due to the small number of photon pulses and due to severe space-charge problems [88] the noise level in the data is very large. M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t 22 Fig.…”
Section: Advances In Highly-parallel 3d Electron Detectionmentioning
confidence: 99%
“…We will now comment on possible saturation of the eCCDs with the very intense FEL pulses. Recent spin-polarized photoemission experiments at FLASH (Fognini et al, 2014) with a single-channel Mott detector have found that more than one electron per pulse reaches the detector of passivated implanted planar silicon (PIPS) which was prohibitive for single-pulse counting. However, these experiments were essentially angle-and energy-integrated, bringing to one detector the whole integral photoemission intensity.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…However, given the very approximate character of this estimate, we cannot rule out that certain pulse energy attenuation may still be necessary. In any case, the problem of single-pulse counting in iMott is less restrictive compared with that of space charge (Fognini et al, 2014), the main encumbrance of photoelectron spectroscopy at FEL sources, which is relieved by an increase of the pulse repetition rate with simultaneous reduction of intensity of each pulse.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…The large mean free path of electrons with kinetic energies above ∼5 keV opens access to bulk properties in hard X-ray PES (HAXPES) experiments. Due to the high pulse intensity of such sources, the Coulomb interaction of the particles released within a single short pulse becomes substantial and can result in prohibitively large energy broadenings [6] and a loss of angular-and even of spin information [7]. This is commonly referred to as the space-charge problem.…”
Section: Introductionmentioning
confidence: 99%